2022
DOI: 10.3390/jpm12121960
|View full text |Cite
|
Sign up to set email alerts
|

Use of High-Frequency Transducers in Breast Sonography

Abstract: Sonography companies have recently developed high-frequency transducers (20–30 MHz) to image the skin and small joints. In this pictorial review, we present a number of settings where these probes can be usefully employed to scan the breast. These include skin abnormalities of the breast and axilla; nipple–areolar complex abnormalities; superficial breast parenchyma abnormalities; breast parenchyma abnormalities in subjects with implants; very small female breasts; peripheral areas in breasts of any size; pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…CEUS has been found comparable to CT and MRI in differentiating FSLs [44,45]. Current US contrast media are blood-pool and their behaviors directly reflect the lesion perfusion, compared with the spleen parenchyma perfusion.…”
Section: Risk Of Malignancy and Pattern Recognitionmentioning
confidence: 87%
“…CEUS has been found comparable to CT and MRI in differentiating FSLs [44,45]. Current US contrast media are blood-pool and their behaviors directly reflect the lesion perfusion, compared with the spleen parenchyma perfusion.…”
Section: Risk Of Malignancy and Pattern Recognitionmentioning
confidence: 87%
“…In very recent articles, there is a controversy concerning the added value of using a gel stand-off pad and high frequency probes (>15 MHz) to better document the vascularization of breast lesions ( 32 , 33 ). The use of a gel stand-off pad serves to augment the separation between the transducer and the intended object, thereby facilitating the alignment of the object within the optimal focal region.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the introduction of 20-MHz probes has contributed substantially in this development ( 32 ). Corvino et al ( 33 ) showed that the high-frequency probe can better visualize the vascularization, nipple-areolar complex abnormalities, and superficial breast parenchyma abnormalities of breast lesions. Thus, ideally, two multifrequency linear probes should be available to perform breast examinations, one with a frequency range from 7.5 to 14 MHz (as suggested by American College of Radiology) and another with an upper frequency of 15 to 24 MHz.…”
Section: Discussionmentioning
confidence: 99%
“…This comprehensive approach improves the diagnostic accuracy while also allowing for more individualized therapy planning and patient care. It also emphasizes the necessity of exploiting technology breakthroughs in breast imaging to improve patient care and results in the field of breast cancer detection and treatment [ 76 ].…”
Section: Future Directionsmentioning
confidence: 99%